2008
DOI: 10.1210/jc.2008-0372
|View full text |Cite
|
Sign up to set email alerts
|

Short Telomeres, Telomerase Reverse Transcriptase Gene Amplification, and Increased Telomerase Activity in the Blood of Familial Papillary Thyroid Cancer Patients

Abstract: Our study demonstrates that patients with FPTC display an imbalance of the telomere-telomerase complex in the peripheral blood, characterized by short telomeres, hTERT gene amplification, and expression. These features may be implicated in the inherited predisposition to develop FPTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 38 publications
7
59
3
Order By: Relevance
“…In addition, we have recently demonstrated in a series of patients with familial papillary thyroid cancer (including also some patients of the present study), an imbalance of the telomeretelomerase complex at the germline level, consisting of short telomeres, increased telomerase copy number, and expression when compared with sporadic papillary thyroid cancer (Capezzone et al 2008). This alteration may contribute (among other as yet unknown abnormalities) to confer genetic predisposition to develop FNMTC and might be involved in the anticipation phenomenon.…”
Section: Capezzone Et Al: Anticipation In Familial Nmtcsupporting
confidence: 63%
“…In addition, we have recently demonstrated in a series of patients with familial papillary thyroid cancer (including also some patients of the present study), an imbalance of the telomeretelomerase complex at the germline level, consisting of short telomeres, increased telomerase copy number, and expression when compared with sporadic papillary thyroid cancer (Capezzone et al 2008). This alteration may contribute (among other as yet unknown abnormalities) to confer genetic predisposition to develop FNMTC and might be involved in the anticipation phenomenon.…”
Section: Capezzone Et Al: Anticipation In Familial Nmtcsupporting
confidence: 63%
“…In this sense, we found an overall low percentage of aneuploid cases, and no differences in DNA ploidy status between familial (whole series and the PTC subgroups) and sporadic PTC were depicted. These findings suggest that chromosomal instability, which could result from the reported telomere length shortening (29,30), is not a common feature in these familial tumours.…”
Section: European Journal Of Endocrinologymentioning
confidence: 79%
“…Aneuploidy is a molecular feature that identifies genetic instability, and potentially, higher metastatic capacity, being commonly associated with worse disease prognosis (26,27). In two recent studies of familial PTC, although controversial (28), Capezzone et al observed shorter telomere length in the leukocytes, other non-neoplastic tissues and tumours in the familial cases when compared with patients with sporadic PTC or healthy subjects (29,30). The size reduction of these nucleoprotein complexes, which protect the ends of chromosomes from degradation and fusion, may induce chromosomal instability, and thus, aneuploidy in these familial tumours.…”
Section: Introductionmentioning
confidence: 99%
“…It is critical to explore molecular biomarkers to guide clinical decision-making with regard to the treatment of GC. TA is thought to be a critical step in the evolution of most tumor types (34)(35)(36)(37), including GC (38,39). Considerable clinical research has been conducted with the aim of assessing the correlation between TA expression and clinicopathological outcome in patients with GC, but the Size Histo T N M TNM >5 cm P/U T3/T4 positive/ positive/ TIII/IV (<5 cm) (W/M) (T1/T2) (negative) (negative) (TI/TII) Liu et al (27) 2008 English China 26 (14) --20 (6) 22 (4) 11 (15) 24 (2) Yang et al (15) 2001 English China 40 (2) 26 (14) 30 (10) 26 (14) 20 (20) -17 (23) Wu et al (17) 2006 English China 52 (12) 23 (29) 49 (3) 40 (12) 37 (15) 14 (38) 33 (19) Hu et al (23) 2004 English China 18 (17) 10 (8) 14 (4) 7 (11) 14 (4) 10 (8) -Zhan et al (31) 1999 English China 81 (13) 46 (35) 43 (38) 68 (13) 51 (30) -60 (21) Hu et al (16) 2009 English China 41 (5) 28 (13) 33 (8) 21 (20) 5 (36) 30 (11) -Wang et al (18) 2004 English China 32 (9) 19 (13) 25 (7) (21) 43 (1) 18 …”
Section: Discussionmentioning
confidence: 99%